Peran Guru Mata Pelajaran Pendidikan Agama Islam dalam Pembelajaram Tata Cara Wudhu pada Siswa Sekolah Khusus Tunarungu Don Bosco Wonosobo - Nofi Listiani; Abdul Majid (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This thesis aims to: 1) Find out the concept of Islamic religious education teachers in learning ablution procedures for students at the special school for the deaf, Don Bosco Wonosobo, 2) Find out what the role of Islamic religious education teachers is in learning ablution procedures for students at the special school for the deaf, Don Bosco Wonosobo. , 3) knowing how to carry out learning ablution procedures for students at the Don Bosco Wonosobo special school for the deaf.This thesis uses a qualitative research approach where the type of research is field research presented with descriptive data. The subjects in this research were Islamic religious education teachers at the Don Boso special school, the principal of the Don Bosco special school and also students at the Don Bosco special school. Technique data collection uses observation methods, semi-structured interviews and also documentation. Data sources were obtained from field research and also qualitative research. The analysis technique used is a data analysis technique, namely the analysis of data that has been collected by researchers through methodological tools. Where data is obtained using a data analysis process in the form of data reduction, data presentation and also conclusions or verification. To test the validity of the data, extended observations, persistence of observations, and triangulation were carried out. The research results show that the concept of Islamic religious education teachers at the Don Bosco special school regarding learning ablution procedures is to emphasize the repetition method where students with hearing impairments have quite short memories which requires teachers to take steps by having students perform ablution practices one by one. The role of the Islamic religious education teacher at the Don Bosco special school is the main factor in students' success in carrying out daily worship, for example introducing ablution material from the pre-primary class. Then, with the implementation of learning about ablution procedures carried out by Don Bosco special school students using the repetition method as well as practice carried out in each learning activity with the aim of increasing students' memory regarding the steps for ablution and also the number of washings in each movement. By practicing ablution one by one, the teacher can find out where each student's mistakes are.